Islamic Religious Education Based on Huma Betang Local Wisdom: A Humanistic Educational Method - Muttaqo, Moh. Ali; Hamdanah, Hamdanah; Normuslim, Normuslim (Darul Yasin Al Sys, 2025)
The integration of local wisdom in education has become an important approach in shaping the character of students. One relevant local wisdom is the philosophy of Huma Betang, which reflects the values of togetherness, deliberation, tolerance, and brotherhood, and aligns with Islamic teachings, especially in the concepts of ukhuwah Islamiyah (Islamic brotherhood), tasamuh (tolerance), and ta'awun (mutual assistance). This research aims to explore how the values of Huma Betang can be integrated into Islamic Religious Education (PAI) learning to create a more humanistic, contextual, and participatory learning system. This type of research is systematic qualitative using the PRISMA approach, which includes searching, filtering, and analyzing field data and literature theories from various relevant sources. The results of the study show that applying Huma Betang values in PAI not only enriches learning methods with local cultural context but also plays a role in building student character that is more tolerant, moderate, and has high social awareness. Furthermore, this approach can bridge the gap between religious teachings and cultural realities of society, thus creating harmony between religious identity and local wisdom. Therefore, the integration of Huma Betang in PAI has the potential to improve the overall quality of education and help students face social and cultural challenges in the era of globalization.